Food carbohydrates : (CRC Press, 2005)
The book provides a comprehensive, single-source reference on the latest advances in food carbohydrates. Its presents both theoretical and practical information; describes analytical methods and structural analysis of polysaccharides; It also introduces conformation and conformation analysis, including information on starch and modified starches.